RGD-modified poly(D,L-lactic acid) nanoparticles enhance tumor targeting of oridonin - Xu J (Dove Medical Press, 2012)
Jie Xu, Ji-Hui Zhao, Ying Liu, Nian-Ping Feng, Yong-Tai ZhangSchool of Pharmacy, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of ChinaObjective: The purpose of this study was to develop an active targeting strategy to improve the therapeutic antitumor efficacy of oridonin (ORI), the main active ingredient in the medicinal herb Rabdosia rubescens.Methods: A modified spontaneous emulsification solvent diffusion method was used to prepare the ORI-loaded atactic poly(D,L-lactic acid) nanoparticles (ORI-PLA-NPs). Surface cross-linking with the peptide Arg-Gly-Asp (RGD) further modified the ORI-PLA-NPs, generating ORI-PLA-RGD-NPs. The NPs were characterized and release experiments were performed in vitro. The pharmacokinetics, tissue distribution, and antitumor activity of the NPs were studied in mice bearing hepatocarcinoma 22 (H22)-derived tumors.Results: The ORI-PLA-NPs and ORI-PLA-RGD-NPs were smooth, sphere-like, and relatively uniform in size. The RGD surface modification slightly increased the mean particle size (95.8 nm for ORI-PLA-NPs versus 105.2 nm for ORI-PLA-RGD-NPs) and considerably altered the surface electrical property (-10.19 mV for ORI-PLA-NPs versus -21.95 mV for ORI-PLA-RGD-NPs), but it had no obvious influence on ORI loading (8.23% ± 0.35% for ORI-PLA-NPs versus 8.02% ± 0.38% for ORI-PLA-RGD-NPs), entrapment efficiency (28.86% ± 0.93% for ORI-PLA-NPs versus 28.24% ± 0.81% for ORI-PLA-RGD-NPs), or the release of ORI. The pharmacokinetic properties of free ORI were improved by encapsulation in NPs, as shown by increased area under the concentration-time curve (11.89 ± 0.35 µg·mL-1 · h for ORI solution versus 22.03 ± 0.01 µg · mL-1 · h for ORI-PLA-RGD-NPs) and prolonged mean retention time (2.03 ± 0.09 hours for ORI solution versus 8.68 ± 0.66 hours for ORI-PLA-RGD-NPs). In the tissue distribution study, more ORI targeted tumor tissue in the mice treated with ORI-PLA-RGD-NPs than with ORI-PLA-NPs or ORI solution. Consistent with these observations, ORI-PLA-RGD-NPs showed greater antitumor efficacy than ORI-PLA-RGD-NPs or ORI solution, as reflected by the decreased tumor growth and the prolonged survival time of mice bearing H22 tumors.Conclusion: The tumor-targeting efficiency and subsequent antitumor efficacy of ORI is increased by incorporation into ORI-PLA-RGD-NPs.Keywords: ORI, antitumor activity, RGD, poly(D,L-lactic acid), nanoparticles